COVID-19 and Clostridioides difficile Coinfection Outcomes among Hospitalized Patients in the United States: An Insight from National Inpatient Database - Rehmat Ullah Awan; Karthik Gangu; Anthony Nguyen; Prabal Chourasia; Oscar F. Borja Montes; Muhammad Ali Butt; Taimur Sohail Muzammil; Rao Mujtaba Afzal; Ambreen Nabeel; Rahul Shekhar; Abu Baker Sheikh (MDPI AG, 2023)
The incidence of Clostridioides difficile infection (CDI) has been increasing compared to pre-COVID-19 pandemic levels. The COVID-19 infection and CDI relationship can be affected by gut dysbiosis and poor antibiotic stewardship. As the COVID-19 pandemic transitions into an endemic stage, it has become increasingly important to further characterize how concurrent infection with both conditions can impact patient outcomes. We performed a retrospective cohort study utilizing the 2020 NIS Healthcare Cost Utilization Project (HCUP) database with a total of 1,659,040 patients, with 10,710 (0.6%) of those patients with concurrent CDI. We found that patients with concurrent COVID-19 and CDI had worse outcomes compared to patients without CDI including higher in-hospital mortality (23% vs. 13.4%, aOR: 1.3, 95% CI: 1.12-1.5, p = 0.01), rates of in-hospital complications such as ileus (2.7% vs. 0.8%, p < 0.001), septic shock (21.0% vs. 7.2%, aOR: 2.3, 95% CI: 2.1-2.6, p < 0.001), length of stay (15.1 days vs. 8 days, p < 0.001) and overall cost of hospitalization (USD 196,012 vs. USD 91,162, p < 0.001). Patients with concurrent COVID-19 and CDI had increased morbidity and mortality, and added significant preventable burden on the healthcare system. Optimizing hand hygiene and antibiotic stewardship during in-hospital admissions can help to reduce worse outcomes in this population, and more efforts should be directly made to reduce CDI in hospitalized patients with COVID-19 infection.